Quantitative Analysis of the DNA Distribution on Cigarette Butt Filter Paper*. Issue 2 (13th February 2013) - Casey, Lisa; Engen, Sarah; Frank, Greg
Abstract The distribution of DNA on the filter paper of smoked cigarette butts was quantitatively mapped using real‐time quantitative polymerase chain reaction. The filter papers from smoked cigarette butts collected from indoor and outdoor sources were sliced into equal pieces and the amount of DNA on each slice was determined. This study found that the cigarette butt filter papers sliced parallel to the seam of the cigarette had more uniformly distributed DNA on the slices and in most cases, there was enough DNA on each slice to obtain a complete DNA profile. The perpendicular slices had a less uniform pattern of distribution and some slices did not have enough DNA to obtain an interpretable DNA profile. Cigarette butts found indoors also had more DNA per cigarette on average than cigarette butts found outdoors.